Human Rights Obligations in FDI Operation: A Paradigm Shift in BITs (Dhaka University Law Journal, 2025)
Incorporation of human rights obligations into bilateral investment treaties (BITs) is rare. However, with the rise of mega investment-related disputes in developing countries, there are growing concerns about the negative impact of foreign direct investment (FDI) on the human rights of the local population from various aspects, directly and indirectly. Apart from jus cogens norms, the international investment law does not impose any direct obligation on human rights in BITs. Therefore, the scope of ‘human rights’ within the present BITs is yet to be determined. There is a pressing need to include human rights obligations in BITs from various corners, including civil society and the UN Conference on Trade and Development (UNCTAD). This paper focuses on the changing paradigm of approaches adopted by the UN, UNCTAD, and scholars in advocating for the inclusion of human rights obligations in the context of FDI operations, mainly referring to the Ruggie Report (2011). The paper focuses on which set of human rights instruments should be referred to as the BITs and the appropriate mechanism to enforce those obligations, as well as addresses the challenges to implement. The paper aims to emphasise the fact that human rights will claim greater significance in future, and countries negotiating BITs will eventually be pushed forward to include human rights obligations, at least in response to growing concerns about the rightfulness of the treaty obligations of the current generation of BITs and the growing demand for more balanced BITs.Dhaka University Law Journal, 2024, 35 (1), 31-52